3D printing–assisted preoperative plan of pedicle screw placement for middle-upper thoracic trauma: a cohort study - Wei Xu; Xuming Zhang; Tie Ke; Hongru Cai; Xiang Gao (BMC Musculoskeletal Disorders, 2017)
Abstract Background This study aimed to evaluate the application of 3D printing in assisting preoperative plan of pedicle screw placement for treating middle-upper thoracic trauma. Methods A preoperative plan was implemented in seven patients suffering from middle-upper thoracic (T3–T7) trauma between March 2013 and February 2016. In the 3D printing models, entry points of 56 pedicle screws (Magerl method) and 4 important parameters of the pedicle screws were measured, including optimal diameter (ϕ, mm), length (L, mm), inclined angle (α), head-tilting angle (+β), and tail-tilting angle (−β). In the surgery, bare-hands fixation of pedicle screws was performed using 3D printing models and the measured parameters as guidance. Results A total of seven patients were enrolled, including five men and two women, with the age of 21–62 years (mean age of 37.7 years). The position of the pedicle screw was evaluated postoperatively using a computerized tomography scan. Totally, 56 pedicle screws were placed, including 33 pieces of level 0, 18 pieces of level 1, 4 pieces of level 2 (pierced lateral wall), and 1 piece of level 3 (pierced lateral wall, no adverse consequences), with a fine rate of 91.0%. Conclusions 3D printing technique is an intuitive and effective assistive technology to pedicle screw fixation for treating middle-upper thoracic vertebrae, which improve the accuracy of bare-hands screw placement and reduce empirical errors. Trial registration The trial was approved by the Ethics Committee of the Fujian Provincial Hospital. It was registered on March 1st, 2013, and the registration number was K2013–03-001.